2006
DOI: 10.1534/genetics.106.057463
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Disruption in Drosophila Bang-Sensitive Seizure Mutants

Abstract: We examined a number of Drosophila mutants with increased susceptibility to seizures following mechanical or electrical stimulation to better understand the underlying factors that predispose neurons to aberrant activity. Several mutations in this class have been molecularly identified and suggest metabolic disruption as a possible source for increased seizure susceptibility. We mapped the bang-sensitive seizure mutation knockdown (kdn) to cytological position 5F3 and identified citrate synthase as the affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 33 publications
3
105
1
Order By: Relevance
“…Although the effects of NDI1 expression on flies were subtle, and did not compromise mitochondrial ATP production to the point of affecting viability or inducing other phenotypes seen in OXPHOS mutants (17)(18)(19), several lines of evidence indicate that the enzyme was constitutively active in vivo, and able functionally to replace complex I, as seen earlier in nematodes, human cultured cells and fungi (8-10, 14, 16). NDI1 expression produced a clear shift in the steady-state ratio of the reduced and oxidized forms of NAD, which provides a possible explanation for its ability to confer significant resistance against paraquat in vivo, as shown earlier in cultured cells (20).…”
Section: Discussionmentioning
confidence: 92%
“…Although the effects of NDI1 expression on flies were subtle, and did not compromise mitochondrial ATP production to the point of affecting viability or inducing other phenotypes seen in OXPHOS mutants (17)(18)(19), several lines of evidence indicate that the enzyme was constitutively active in vivo, and able functionally to replace complex I, as seen earlier in nematodes, human cultured cells and fungi (8-10, 14, 16). NDI1 expression produced a clear shift in the steady-state ratio of the reduced and oxidized forms of NAD, which provides a possible explanation for its ability to confer significant resistance against paraquat in vivo, as shown earlier in cultured cells (20).…”
Section: Discussionmentioning
confidence: 92%
“…On the basis of evoked electrical seizure activity in the giant fiber pathway, two loosely defined classes of bang-sensitive mutants have been distinguished (Pavlidis and Tanouye 1995;Fergestad et al 2006a). Type I seizures, which are thought to originate upstream of flight muscle motor neurons, are characterized by 10-to 30-Hz spike trains that lack any clear pattern and terminate abruptly.…”
Section: Resultsmentioning
confidence: 99%
“…This idea is further supported by the reduced threshold for electrically induced seizures in these mutants (Kuebler and Tanouye 2000). Molecular identification of several of these mutants has suggested that they result from defects in mitochondrial metabolism (Royden et al 1987;Zhang et al 1999;Fergestad et al 2006a), similar to metabolically linked seizures in humans (reviewed in Simon and Johns 1999;De Vivo 2002;Van Gelder and Sherwin 2003;Patel 2004). Seizures exhibited by these mutants respond to anticonvulsant drugs used in vertebrates (Kuebler and Tanouye 2002;Reynolds et al 2004;Tan et al 2004), further demonstrating that many of the molecular mechanisms mediating neuronal activity are conserved.…”
Section: T He Epilepsies and Neurodegenerative Disordersmentioning
confidence: 95%
See 1 more Smart Citation
“…Recordings from the giant-fiber (GF) escape circuit were performed as previously described (33)(34)(35). Briefly, the animals were etherized, mounted in clay with the head and thorax exposed, and then placed in a humidified chamber for at least 20 minutes to allow recovery.…”
Section: Methodsmentioning
confidence: 99%